Supervivencia relativa de las razas II y XXII de Hemileia vastatrix - Rodriguez M, K.D.=700 1 Moreno R, G.
(Es, En)
Ilus., 15 ref.
Keywords: COFFEA ARABICA; HEMILEIA VASTATRIX; HONGOS; ESPECIES; SUPERVIVENCIA; SELECCION; COLOMBIA; AGRESIVIDAD